Spatial and contextual long-term and working memory in ageing and disease - Gurau, O (2021)
Initially thought to be two independent memory systems, working memory (WM) and long-term memory (LTM) both present associative features controlled by the medial temporal lobe (MTL). Despite their similarities, the two memory systems have mostly been explored and compared using distinct methods and measures. Considering their differences and their correspondences, this thesis focuses on spatial associative WM and LTM performance in healthy ageing and in the presence of MTL impairment. The studies presented investigate the mechanisms of the two memory systems, their interplay, and the modulatory relationship between them and attention, using analogous tasks and equivalent behavioural measures. Specifically, Chapter 2 explores if retro-cueing benefits, previously observed in WM, extend to LTM retrieval, and whether this could represent a means of ameliorating age-related LTM impairment. Next, in Chapter 3, I compare the performance of young and older healthy adults in a spatial memory task on two devices – a personal computer and an immersive VR device – to test whether old adults benefit from an increased level of immersion and determine the optimal methods of measuring spatial memory. In the second study, I use a navigation-based memory task measuring WM and LTM, to investigate their patterns of use and interplay that might change with ageing. Lastly, Chapter 4 relies on the same task and aims to analyse patterns of performance modulated by different levels of MTL impairment in old healthy adults and individuals with limbic encephalitis. The results propose that WM and LTM show age-related associative deficits and that their interplay is preserved in ageing, despite old adults’ increased forgetting. Additionally, they suggest that WM and LTM may rely on different retro-cueing mechanisms. Lastly, the most noteworthy outcomes are the tasks developed to measure spatial associative memory of different timespans in equivalent ways, using analogous steps and stimuli, which can become great tools in the research of WM and LTM retrieval processes.